Prospective study of guideline‐tailored therapy with direct‐acting antivirals for hepatitis C virus‐associated mixed cryoglobulinemia. Issue 5 (29th August 2016) - Gragnani, Laura; Visentini, Marcella; Fognani, Elisa; Urraro, Teresa; De Santis, Adriano; Petraccia, Luisa; Perez, Marie; Ceccotti, Giorgia; Colantuono, Stefania; Mitrevski, Milica; Stasi, Cristina; Del Padre, Martina; et al.
Abstract : Hepatitis C virus (HCV)‐associated mixed cryoglobulinemia (MC) vasculitis commonly regresses upon virus eradication, but conventional therapy with pegylated interferon and ribavirin yields approximately 40% sustained virologic responses (SVR). We prospectively evaluated the efficacy and safety of sofosbuvir‐based direct‐acting antiviral therapy, individually tailored according to the latest guidelines, in a cohort of 44 consecutive patients with HCV‐associated MC. In two patients MC had evolved into an indolent lymphoma with monoclonal B‐cell lymphocytosis. All patients had negative HCV viremia at week 12 (SVR12) and at week 24 (SVR24) posttreatment, at which time all had a clinical response of vasculitis. The mean (±standard deviation) Birmingham Vasculitis Activity Score decreased from 5.41 (±3.53) at baseline to 2.35 (±2.25) ( P < 0.001) at week 4 on treatment to 1.39 (±1.48) ( P < 0.001) at SVR12 and to 1.27 (±1.68) ( P < 0.001) at SVR24. The mean cryocrit value fell from 7.2 (±15.4)% at baseline to 2.9 (±7.4)% ( P < 0.01) at SVR12 and to 1.8 (±5.1)% ( P < 0.001) at SVR24. Intriguingly, in the 2 patients with MC and lymphoma there was a partial clinical response of vasculitis and ∼50% decrease of cryocrit, although none experienced a significant decrease of monoclonal B‐cell lymphocytosis. Adverse events occurred in 59% of patients and were generally mild, with the exception of 1 patient with ribavirin‐related anemia requiring blood transfusion. Conclusion: Interferon‐free, guideline‐tailored therapy with direct‐acting antivirals is highly effective and safe for HCV‐associated MC patients; the overall 100% rate of clinical response of vasculitis, on an intention‐to‐treat basis, opens the perspective for curing the large majority of these so far difficult‐to‐treat patients. (Hepatology 2016;64:1473‐1482)